Design and Construction of a Pesticide Spraying Machine for Chili Plants on Ridge fields - Wisnaningsih Wisnaningsih; Muhammad Iqbal Maulana; Wawan Hermawan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
Pest and disease attacks on chili plants are typically handled by pesticide spraying using backpack sprayers, which pose health risks to operators due to pesticide exposure and the weight of the equipment. The proposed solution is the development of a remote-controlled pesticide sprayer designed for ridged fields. This machine is equipped with a frame, track-type wheels, a drive motor, a water tank, a water pump, and navigation using a First Person View (FPV) camera. The machine is controlled via a remote control with a range of up to 200 meters. Performance testing shows that the machine moves at an average speed of 0.30 m/s, with an average track wheel slip value of 8.32% and a maximum slip of 10.65% when carrying a full water tank. The machine is equipped with 4 nozzles positioned as needed, with an average flow rate of 0.87 L/minute. The average current required for the driver motor is 9.1 A, while the current for the pump remains stable at 2.14 A. The control system consists of a cytron motor driver for the drive motor and a relay for controlling the on/off function of the water pump.